Implementation Of Transformative Learning Model Through Parents For Early Childhood Parenting In Java Family - Novya, Hany; Alfiani Aisyah, Nafisya (KnE Social Sciences, 2017)
Early childhood parenting in a family is a process fraught with problems and transformative states. One of the cases is ‘anak karbitan’ (adultish child) as a result of parents’ ambition which is prevalent in urban areas, while in rural areas many parents do a variety of mistakes in parenting. It is caused by a lack of parental understanding on the parenting ideal knowledge. This study aims at finding the transformative learning process that occurs in the early childhood parenting in a family environment. The researcher employs a qualitative approach with a case study design. The informants of this study were parents who had children aged 0-6 years. The processes of data collection involved in-depth interviews, group discussions, participatory observation, and documentation. The researcher used the interactive analysis models to analyze the data. The results showed that parents did not realize that the learning experience they had, give transformative impact on their parenting style their children in their family environments. The problems faced by the parents in early childhood parenting were those dealing with: (1) with the unique character of the child, (2) the habituation of a child, (3) training the children’s independence, discipline, and responsibilities, (4).the child’s social interaction, (5) training their children’s confidence, (6) sex education of early childhood. The actions that the parents did to solve their problem were giving rewards, advice, warnings, and punishment, and neglecting their children. Transformative impacts that occurred on the parents were internal and external impacts. Keywords: transformative learning, early childhood, parenting, parents